Takamul Nataij al-Tarbawiyyah Muta’addadah al-Tsaqafat fi Dirasah al-Lughah al-‘Arabiyyah li al-Thullab - Ubadah, Ubadah; Wanto, Deri (Arabiyatuna: Jurnal Bahasa Arab, 2022)
This research was conducted to determine the implications for multicultural educational outcomes, especially in the study of the Arabic language for students at Insan Cendekia Governmental Intermediate School in the city of Palu. The integration of multicultural pedagogical outcomes into learning is a pressing issue that is also important to study, especially concerning its impact on students at schools. This research adopted a case study with a qualitative approach. Research data were garnered from observation, in-depth interviews, and written documents. The findings indicated that the implications of the integration of multicultural educational results in the study of the Arabic language showcased the existence of multicultural attitudes that students exhibited in the form of internal and external actions.